Subordinasi dan Emansipasi Perempuan dalam Novel Al-Hujurat Karya Sherine Sami (Kajian Feminisme Marxis) - Muhammad Mahdi; Mohamad Rohman (Yayasan Haiah Nusratul Islam, 2026)
This study aims to analyze women's subordination and emancipation in the novel Al-Hujurat by Sherine Sami using the Marxist feminism approach. The method used is qualitative descriptive with the novel as the data source. Data collection techniques were carried out through reading and note-taking, while data analysis used Marxist feminism concepts. The results show that the female character experiences subordination in the forms of patriarchal system, exploitation, social reproduction, economic dependency, gender-based division of labor, alienation, and internalization of patriarchal ideology. However, the female character also undergoes an emancipation process through critical consciousness (class consciousness) that emerges gradually, from questioning injustice, recognizing patterns of repeated violence, to making decisions to save herself and determine her own destiny. Thus, the novel Al-Hujurat not only depicts women's subordination within the patriarchal system but also demonstrates that critical consciousness can become the foundation for emancipation toward liberation from oppressive structures.